Islamic Economics and Labor: Management Balances Social Justice and Economic Efficiency - Aris Budiman; Ayus Ahmad Yusuf (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
In this article, I explore the intersection between Islamic economics and employment, in particular focusing on how its principles can address global employment challenges while driving social justice and economic efficiency. I argue that the integration of wealth redistribution mechanisms, ethical finance, and skills development can create inclusive employment opportunities that improve social equality and overall economic productivity. By analyzing the role of Zakat and Waqf in creating jobs, I show how Islamic financial principles such as profit sharing and partnerships can encourage sustainable employment practices. Furthermore, I investigated the importance of skills development through Islamic education initiatives in encouraging the formation of human resources. My findings suggest that Islamic economic frameworks have significant potential to address contemporary employment issues while advancing broader social justice and sustainability goals.